'Everybody's gotta do something': neutrality and work. Issue 7 (9th November 2020) - Jenkins, David
ABSTRACT: Work is something with which most people have to engage. For many of us, it is also something towards which we feel ambivalent or worse. In this paper, I argue for the need to think about the meaning of this ambivalence when discussing the issue of state neutrality and the justification of state's decisions as they pertain to the economy. Where the kinds of work some people have to perform issue in costs extensive enough to undermine their integrity, the neutrality of a state's decision is insufficient justification. In these circumstances, states must find ways to grant such workers an exemption, allowing them to renegotiate the extent and quality of the work they do. I examine unconditional basic income as a means of fulfilling this function.